Disintegration of large balls of water-based liquids in free fall through high-temperature gases; Atomization and Sprays; Vol. 27, iss. 10 - Strizhak P. A. Pavel Alexandrovich; Volkov R. S. Roman Sergeevich; Zabelin M. V. Maksim Valerievich; Piskunov M. V. Maksim Vladimirovich (2017, 2017)
Title screen